2016
DOI: 10.1111/desc.12388
|View full text |Cite
|
Sign up to set email alerts
|

Trust matters: Seeing how an adult treats another person influences preschoolers' willingness to delay gratification

Abstract: Holding out for a delayed reward in the face of temptation is notoriously difficult, and the ability to do so in childhood predicts diverse indices of life success. Prominent explanations focus on the importance of cognitive control. However, delaying gratification may also require trust in people delivering future rewards as promised. Only limited experimental work has tested this idea, and such studies with children were focused on general reward expectations, so evidence was ambiguous as to whether social t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 79 publications
(95 reference statements)
3
61
0
2
Order By: Relevance
“…For instance, Vaish, Carpenter, and Tomasello (2016) found that after 3-year-old children had caused someone harm, they showed reparative behavior immediately after the mishap but not during later phases of the procedure and not in novel contexts. Similarly, Michaelson and Munakata (2016) found that 3-to 5-year-olds were more willing to delay gratification for a reward promised by a trustworthy experimenter than by a non-trustworthy experimenter, but this differentiation did not carry over into a subsequent preference task. Together, these findings suggest that young children's social evaluations and responses affect their immediate behavior but might not carry over into later or novel situations.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Vaish, Carpenter, and Tomasello (2016) found that after 3-year-old children had caused someone harm, they showed reparative behavior immediately after the mishap but not during later phases of the procedure and not in novel contexts. Similarly, Michaelson and Munakata (2016) found that 3-to 5-year-olds were more willing to delay gratification for a reward promised by a trustworthy experimenter than by a non-trustworthy experimenter, but this differentiation did not carry over into a subsequent preference task. Together, these findings suggest that young children's social evaluations and responses affect their immediate behavior but might not carry over into later or novel situations.…”
Section: Discussionmentioning
confidence: 96%
“…We agree that contextual factors are important for understanding and addressing socioeconomic profiles of present-oriented behavior. Our work has highlighted the role of social norms and social trust: Children will delay gratification when they see that members of their own group do so (Doebel & Munakata 2017), and children and adults prefer immediate rewards when they believe those controlling the rewards are untrustworthy (Michaelson et al 2013;Michaelson & Munakata 2016; see also Kidd et al 2013;Lee & Carlson 2015). We have thus argued that presentoriented behaviors cannot be understood solely in terms of selfcontrol abilities (i.e., willpower).…”
Section: Sabine Doebel Laura E Michaelson and Yuko Munakatamentioning
confidence: 94%
“…Knowledge may include specific concepts that make a particular goal more appealing or easy to keep in mind (e.g., mental state concepts that help one tune into others' expectations or desires, Wellman, Cross, & Watson, 2001); relevant motor, procedural, and embodied knowledge (Goldstein & Lerner, 2018;Lillard, 2016); verbal concepts, skills, rules or strategies (Doebel, Dickerson, Hoover, & Munakata, 2018;Winsler, Fernyhough, & Montero, 2009); and even knowledge about others' control behavior (Leonard, et al, 2018). Beliefs may include ideas about how one's group behaves in relation to similar goals (e.g., or expectations about the likely benefits or consequences of using control (Kidd, Palmieri, & Aslin, 2013;Michaelson & Munakata, 2016). Values and norms may include ideas about when and how control should be used (e.g., Carlson & Zelazo, 2011;Lamm et al, 2018).…”
Section: An Alternative View: Executive Function Development As Skillmentioning
confidence: 99%
“…However, beliefs, values, and other mental content may also shape these children's performance on executive function measures. For example, a belief that the environment and the people in it are not reliable may affect how well control is engaged in particular contexts (Kidd, et al, 2013;Michaelson & Munakata, 2016;Ma, Chen, Xu, Lee, & Heyman, 2018). Children may also struggle to use control in contexts that have questionable significance for them in part because of the absence of prior experience to suggest that rewards are forthcoming (Michaelson & Munakata, in press;Pepper & Nettle, 2018).…”
Section: New Ideas About Interventions To Improve Executive Functionmentioning
confidence: 99%